Favela's young cultural producers - Tommasi, Maria Livia de (2016)
In this paper, I analyze the material collected as part of an ethnographic research that I develop since 2010 in Rio de Janeiro, in the context of which I’ve made some thematic interviews with young cultural producers who are slum’s dwellers. Listening to their testimonies, watching their practice, I seek to understand the specificity of these activities, the qualities required to exercise them and the obstacles faced. I set my questions in the context of the centrality assumed by the field of culture as a resource, as part of the operations of urban re-qualification and in the context of the transformations that have occurred in labor market. The slums (favelas), historically considered territories of poverty and violence, are now celebrated as territories of opportunity.